Implementation of the Poor Community Empowerment Policy (A Study on the Family Hope Program in Palembang City) - Deffi Haryani (Spirit Publik: Jurnal Administrasi Publik, 2021)
This research describes and analyzes the factors causing the ineffective implementation of the empowerment policy for the poor, through the process of implementing the “Family Hope Program”. This research was conducted in Palembang City. The research method used in this study was a qualitative method, because the researchers themselves were directly involved in the research process, including serving as the participant of observation. The research design used was "analytic descriptive design", the method of examining an object of events in the present. The results of research show that the implementation of the empowerment policy for the poor has not been effective. This is due to 3 (three) environmental factors: 1) Actors and arenas, the main aspect of which is the poor’s limited ability of managing the potential resources available in increasing the income of the poor; 2) organizational structures and bureaucratic norms, where the main aspect causing it is that structurally the Family Hope Program is not linked to community institutions in each District, 3) Communication networks and adjustment mechanisms, where the main aspect causing it is the ineffective communication and relationships between actors and elites in the District, Kelurahan, stakeholders and opinion leaders.